The Influence of English Communication Competence and Learning Motivation on Employability Skills with Learning Engagement as a Mediating Variable - Arifin Arifin (SEAN Institute, 2026)
This study aims to examine the effects of English Communication Competence and Learning Motivation on Employability Skills, with Learning Engagement serving as a mediating variable among Tax Accounting students at Universitas Pamulang. A quantitative research approach was employed using a survey method. Data were collected from 50 undergraduate students through a structured questionnaire measured on a seven-point Likert scale. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3.0. The results indicate that English Communication Competence has a positive and significant effect on Employability Skills, while Learning Motivation has a positive and significant effect on Learning Engagement. However, English Communication Competence does not significantly affect Learning Engagement, Learning Engagement does not significantly affect Employability Skills, and Learning Motivation does not significantly affect Employability Skills. Furthermore, the mediation analysis reveals that Learning Engagement does not mediate the relationship between English Communication Competence and Employability Skills, nor the relationship between Learning Motivation and Employability Skills. These findings highlight that English communication competence is the primary determinant of students' employability skills, whereas learning motivation mainly contributes to increased learning engagement without directly enhancing employability. The study suggests that higher education institutions should strengthen English communication competence through workplace-oriented learning to better prepare graduates for the demands of the global labor market.